Zinc uptake in rice (Oryza sativa)-wheat (Triticum aestivum) cropping system under the influence of microbial consortia (Pusa decomposer) mediatedin situ rice straw management options - MANU, S M; SINGH, Y V; SHIVAY, Y S; SHEKHAWAT, KAPILA; SHARMA, V K; SAHA, NAMITA DAS; DINESH, GOVINDARAJ KAMALAM (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the rainy (kharif) and winter (rabi) seasons of 2019–20 and 2020–21 at research farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of various crop establishment methods and microbial consortia (Pusa decomposer) mediated in situ rice straw management options on zinc (Zn) concentration and uptake in rice (Oryza sativa L.) (cv. Pusa Basmati 1509) and wheat (Triticum aestivum L.) (cv. HD 2967). The experiment was laid out in split-plot design (SPD) with 3 replications having 2 main plot (main factor) treatments, viz. aerobic rice (AR); and conventional transplanted (CT) rice in wet season; and 7 sub- plot (sub-factor) treatments, viz. Clean cultivation (removal of paddy straw); Paddy straw incorporation (PSI); Paddy straw mulching (PSM); PSI + Pusa decomposer (PD); PSM + PD; PSI + urea @20 kg/ha; and PSI + PD + urea @10 kg/ha in dry season. Findings showed that, in rice the zinc concentration (18.51 and 20.30 mg/kg in grain; 57.02 and 57.81 mg/kg in straw) and uptake (78.38 and 89.81 g/ha in grain; 427.1 and 434.6 g/ha in straw) were significantly superior in CT rice than AR in main plots during both the years of experiments. However, sub-plot treatments were non-significant in the zinc concentration and uptake. In wheat, among in situ rice straw management options (sub- plots), paddy straw incorporation + Pusa decomposer + Urea @10 kg/ha treatment significantly resulted in higher Zn concentration (38.08 and 39.03 mg/kg in grain; 28.24 and 29.01 mg/kg in straw) and uptake (185.0 and 191.9 g/ha in grain; 234.2 and 242.6 g/ha in straw) compared to other treatments and control (clean cultivation). The principal component analysis revealed that Zn uptake positively correlated with straw and grain yields in rice and wheat. Thus, the same treatment was found to be a better option for higher Zn concentration and uptake in the rice-wheat cropping system.